ANÁLISE DE NOVOS ESPÉCIMES DO GÊNERO LEPIDOTES SP. PARA O MUNICÍPIO DE FLORIANO, PIAUÍ, BRASIL - Moura, Francisca Raiany Soares de; Figueiredo, Ana Emilia Quezado de; Fortier, Daniel Costa (Revista Nordestina de Zoologia, 2017)
The genus Lepidotes has been studied by several authors because it has a wide geographic distribution, occurring in all continents, except Antarctica. In order to analyze new specimens from the Parnaíba Basin, field works were carried out in a new outcrop in the municipality of Floriano-PI. In this locality, three incomplete specimens and a few isolated scales, belonging to the Pastos Bons Formation of Juro-Cretaceous age, were collected. It is possible to describe the specimens presented in this work as of the genus Lepidotes because they present a cranial anatomy, the morphology of the scales and the presence of a scale pattern similar to the specimens described in the literature. The specimens described increase the records of this genus for the paleoichthyofauna of the basin.